ECONOMIC GROWTH AND FDI EQUITY-DEBT COMPOSITION: A BIBLIOMETRIC INSIGHT - Che Dan, Siti Sarah; Khalid, Norlin; Mohd Azam, Abdul Hafizh (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Foreign direct investment (FDI) is a vital driver of economic growth, but most research only looks at total inflows, ignoring the split between equity and debt. This gap is important because equity and debt react differently to macroeconomic conditions and have different impacts on financial stability and long-term growth. This study uses a bibliometric analysis to examine research on economic growth and FDI equity–debt composition. Using Scopus data (2020–2025) with 1,110 articles, the dataset was cleaned with OpenRefine, analyzed with Scopus Analyzer, and visualized in VOSviewer. Results show a consistent rise in publications, with China, India, Vietnam, Malaysia, and Pakistan as major contributors. Highly cited works focus on sustainability, renewable energy, and green innovation, while the equity–debt aspect remains less explored. Overall, this study maps global research trends, identifies influential contributors, and underscores the need for more in-depth analysis of FDI composition to better understand its role in fostering sustainable economic growth.